A HYBRID PEDAGOGICAL APPROACH TO DEVELOPING PROFESSIONAL COMMUNICATION COMPETENCE IN UNIVERSITY STUDENTS - Gulbahor Maxdiyevna Mansurova (Bright Mind Publishing, 2025)
This article examines the combination of traditional and modern teaching methods in higher education to prepare students for professional communication. While lectures, seminars, and lab sessions provide essential knowledge, interactive approaches—such as situational exercises, role-playing, case studies, professional training, and project-based tasks—immerse students in realistic professional contexts. Emphasizing the “show – present to simulate” principle, educators must assess students’ readiness and apply preventive pedagogical strategies to support active participation and practical skill development.
Keywords: Higher education, German as a foreign language, professional communication, interactive learning, role-playing, case studies, project-based learning, competence-based education, communicative approach